RELEVANSI PERJANJIAN PRANIKAH ANTARA HUKUM NEGARA DAN HUKUM AGAMA - Haqkida Kancana Suhendri (Universitas Muhammadiyah Metro, 2020)
This research aims to determine the extent to which the relevance of the pre-marital agreement between the law of the State and the Islamic law because in the community there are legal dualism which both govern the prenup agreement so it is important to He did this research to provide a general explanation of the relevance of the premarital agreement between the law of the country and the Islamic religious law. This research uses the type of empirical approach that the business approaches the problems examined by the real legal nature or in accordance with the reality that lives in society as a deepening of the context of the problems investigated for Provide a comprehensive understanding. The results showed that the relevance of the pre-marital agreement between the law of the country and the Islamic law of the two are still intertwined governing the general agreement. In particular, a pre-marital agreement is a binding legal relationship between a candidate husband and wife containing the details of the agreement filed by the parties that apply as a law. Both state law and Islamic law provide a fairly clear legal basis to make a premarital agreement, regulate the boundaries of the things that can be promised and settlement mechanisms in case of something undesirable Day.